Preparation and Characterization of NiMo/C Using Rapid Heating and Cooling Method for Renewable Diesel Synthesis from Nyamplung Oil (Calophyllum Inophyllum Oil) - Bambang Heru Susanto; Muhammad Bagus Prakasa; Muhammad Husein Shahab (Universitas Lampung, 2017)
Abstract— The synthesis of metal nanocrystal was conducted by modification preparation from simple heating method which heating and cooling process run rapidly. By used NiMo/C 700 oC catalyst for 30 minutes which had surface area of 263.21 m2/gram, had 31.77 nm crystal size, and good morphology of material, obtained catalyst with high activity, selectivity, and stability. After catalyst activated, synthesis of renewable diesel performed in hydrodeoxygenation reactor at 375 oC, 12 bar, and 800 rpm for residence time of 150 minutes. The result of conversion was 81.99 %, yield was 68.08%, selectivity was 84.54 %, and spesification met the petroleum diesel standard.Keywords— Hydrodeoxygenation, NiMo/C, Nyamplung Oil, Rapid Heating and Cooling, Renewable Diesel.